A comprehensive threat analysis to support the red list of marine and coastal ecosystems of Colombia - Uribe, Edwin S.; Etter, Andrés; Luna-Acosta, Andrea; Diazgranados, María Claudia; Alonso, David; Chasqui, Luis; Osorno, Adriana; Acosta, Alberto; Rodríguez-Rodríguez, Alexandra; Ricaurte-Villota, Constanza; Escobar, Luisa; Giraldo, Alan (Frontiers in Marine Science, 2022)
Human activities represent a growing threat to biodiversity, increasing species extinction and leading to ecosystems’ collapse. Colombia is a megadiverse country, and almost half of its territory is marine. However, Colombia’s marine and coastal ecosystems are constantly impacted by anthropogenic and climatic threats. Knowledge of the spatial distribution of threats to ecosystems is fundamental to understanding their risk of collapse assessed by the Red List of Ecosystems, an IUCN global standard to guide conservation and management action. This study provides a quantitative map assessment of a set of key anthropic and climatic threats and impacts to the marine-coastal area of Colombia, with the aim to perform the threat description component of the Red List assessment protocol. A spatial model was elaborated under the methodological framework of Cumulative impact assessment to analyze the threat level and impact level of 12 anthropogenic and climatic threats. Threat level results meet the expected spatial patterns, where the Caribbean Sea is more threatened than the Pacific Ocean, and continental areas are more threatened than the oceanic ones. When impact level is analyzed, habitat transformation and sea warming were the threats with the most impact on coastal and marine ecosystems, respectively. The assessed climatic threats were highly extent throughout the study area, They occur even in the most pristine areas (e.g., Malpelo Island). Climate threats are challenging to national conservation strategies since these pressures are not completely manageable at local scales, as they depend mainly on global efforts. Recommendations drawn from this work can guide actions for the conservation of the ecosystems of Colombia.